Legal Sanctions for Health Protocol Violations During the Covid-19 Pandemic In Law Enforcement Perspective - Febrianto, Ronal (Green Publisher, 2022)
The spread of the Corona virus does not only attack human health, the new Corona virus also causes the economic decline of countries in the world. Public understanding and awareness of COVID-19 prevention is still low. In addition, the level of community compliance to carry out social distance is also still low. In this research, the author gives an example of a case of a crowd in Petamburan and in Megamendung where the defendant is Muhammad Habib Rizieq Shihab (MHRS) whose case has been sentenced by the East Jakarta Court. The research method that the author uses is the normative juridical method, namely research using library data, carried out by searching, citing, recording, inventorying, analyzing, and studying data in the form of library materials needed and related to legal sanctions for violators of health protocols in Indonesia. during the Covid 19 pandemic. Based on the results of the study, the authors conclude that the mechanism of action in the context of law enforcement against people who violate the health protocol during the Covid 19 pandemic is prioritized more on administrative sanctions which in this case are regulated as sanctions for violations of the health.